2018
DOI: 10.3390/atmos9090331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Northern Hemisphere Atmospheric Blocking on Arctic Sea Ice Decline in Winter at Weekly Time Scales

Abstract: Abstract:In this study, the effects of the Northern Hemisphere atmospheric blocking circulation on Arctic sea ice decline at weekly time scales are examined by defining four key regions based on observational data analysis. Given the regression analysis, the frequently occurring atmospheric patterns related to the sea ice decline in four key sea regions (Baffin Bay, Barents-Kara Seas, Okhotsk Sea and Bering Sea) are found to be Greenland blocking (GB), Ural blocking (UB), western Pacific blocking (PB-W) and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
(46 reference statements)
3
9
1
Order By: Relevance
“…The regions of cold and warm anomalies found in this study are in accordance with Papritz and Grams (), who pointed out more cold outbreaks in the Norwegian Sea during the regime GB and in southern Greenland during the regime Zo. Our results also corroborates the study of Yao et al () identifying strong warm anomalies increased by downwards IR over the western part of high‐pressure systems.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The regions of cold and warm anomalies found in this study are in accordance with Papritz and Grams (), who pointed out more cold outbreaks in the Norwegian Sea during the regime GB and in southern Greenland during the regime Zo. Our results also corroborates the study of Yao et al () identifying strong warm anomalies increased by downwards IR over the western part of high‐pressure systems.…”
Section: Discussionsupporting
confidence: 93%
“…The regime contribution to the temperature trend is low compared to Norway or northeastern Canada, which can be attributed to a very low inter‐regime variability in terms of atmospheric water content and downwards IR anomalies (Figure ). The low contribution of atmospheric circulation in the Spitsbergen warming seems to be in contradiction with previous studies stating that EB is associated with high temperature in this region, due to advections of wet air increasing downwards IR (Luo et al , ; Rinke et al , ; Yao et al , ). Dahlke and Maturilli () estimate that 22% of the warming in Ny Ålesund (Spitsbergen) relates to an increase of EB.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The Ural blocking with the positive (negative) phase of NAO is associated with higher (lower) intrusion of moisture into the BKS region (Luo et al, , statistically significant at the 95% confidence level from the Student's t‐ test). Yao, Luo, and Zhong () associated atmospheric blocking in the northern hemisphere with a decline in sea ice. They reported that blocking the circulation strengthens the transport of moisture and heat to the Arctic system (significant at the 95% confidence level).…”
Section: Drivers Of Observed Changes In Moisture Transport To the Arcmentioning
confidence: 99%
“…However, the short observational period (40 years) relative to the time scales of AMO or PDO is difficult to find statistically significant relationships between the weather systems and decadal oceanic modes of variability [16]. On the other hand, the literature [28] indicates that the sea ice cover (SIC) is closely related to blocking frequency. The composite SIC anomaly in January during three periods conclude that the sea ice cover area in the Bering Sea is lower (higher) in the higher (lower) blocking frequency period.…”
Section: Discussionmentioning
confidence: 99%